2003
DOI: 10.1002/ejoc.200300471
|View full text |Cite
|
Sign up to set email alerts
|

Topochemical [2+2] Dimerization of Kinetically Stabilized 1‐Phosphaallenes in the Solid State

Abstract: The thermolysis of two bulky 1‐phosphaallenes in the solid state afforded diphosphanylidenecyclobutane or 2,4‐dimethylene‐1,3‐diphosphacyclobutane. The regioselectivity of the [2+2] dimerization depends largely on the crystal structure of the 1‐phosphaallenes, and the reaction path seems to be affected by the presence of bulky 2,4,6‐tri‐tert‐butylphenyl (Mes*) group. This topochemical reaction was also controlled by the substituents at the 3‐position of the 1‐phosphaallene skeleton. (© Wiley‐VCH Verlag GmbH & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The molecular structures of the colourless compounds 25 to 28 (Figure ) reveal the expected P=C=C motif with P=C (163.4 pm) and C=C distances (131.6 pm) in the typical ranges. In accordance with results reported in the literature the P=C=C groups deviate slightly from linearity with P1−C1−C2 angles of 171° on average. The C4−P1−C1 angles including the ipso ‐C atoms of the supermesityl groups are 103°.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The molecular structures of the colourless compounds 25 to 28 (Figure ) reveal the expected P=C=C motif with P=C (163.4 pm) and C=C distances (131.6 pm) in the typical ranges. In accordance with results reported in the literature the P=C=C groups deviate slightly from linearity with P1−C1−C2 angles of 171° on average. The C4−P1−C1 angles including the ipso ‐C atoms of the supermesityl groups are 103°.…”
Section: Resultsmentioning
confidence: 97%
“…With exception of the cyclohexyl compound 28 the aromatic rings of the supermesityl groups show the usual deviation from planarity with the ipso ‐C atoms 13 pm above the plane of the remaining five C atoms. With Mes*‐P=C=CH 2 and the corresponding compound bearing a cyclopropyl ring instead of a H atom the structures of only two 3H‐phosphaallenes are reported in the literature; the structures of the text book compounds 25 and 26 were obtained more than 30 years after first reports on their syntheses …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Exceptions are solid butatrienes that stereospecifically give the radialene upon heating [148], or the further examples in Ref. [149], or 1-phospha-allenes [150]. In addition, the solid-state milling of C 60 with KCN catalysis to give 18% of C 120 appears to be a [2 + 2]-dimerization (not shown in Scheme 18) [151].…”
Section: Linear Polymerizationsmentioning
confidence: 99%
“…702 Kinetically stabilised 1-phosphaalkenes have been shown to undergo a topochemical [2þ2] dimerisation on heating in the solid state to form either diphosphanylidenecyclobutanes or 2,4-dimethylene-1,3-diphosphacyclobutanes. 703 The electronic properties of the phosphaarsaallene Mes*P¼C¼AsMes* (and the related diarsaallene) have been studied using UV photoelectron spectroscopy and theoretical methods. 704 Theoretical studies have also been reported for the 1,4-diphosphabuta-1,3-diene 705 and 2,3-diphosphabuta-1,3-diene 706,707 systems.…”
Section: P P -Bonded Phosphorus Compoundsmentioning
confidence: 99%